2010
DOI: 10.1158/1078-0432.ccr-09-3185
|View full text |Cite
|
Sign up to set email alerts
|

Bcl2 and Human Papilloma Virus 16 as Predictors of Outcome following Concurrent Chemoradiation for Advanced Oropharyngeal Cancer

Abstract: Purpose: Oropharyngeal squamous cell carcinoma (OPSCC) associated with human papilloma virus (HPV) is rapidly growing in incidence. Despite better prognosis than OPSCC associated with traditional risk factors, treatment failure still occurs in a significant proportion of patients. We had identified the antiapoptotic protein Bcl2 as a marker for poor outcome in advanced OPSCC treated with concurrent chemoradiation. To determine whether Bcl2 and HPV together might further characterize treatment response, we exam… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
45
0

Year Published

2011
2011
2015
2015

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 60 publications
(49 citation statements)
references
References 32 publications
4
45
0
Order By: Relevance
“…Other centres choose to test for p16 alone, followed by further direct HPV testing if p16 results are unclear or negative [30][31][32]. Research groups have also looked into other molecular markers that may act as further prognostic and/or treatment factors, such as Bcl2 [33]. Recently, RNA in situ hybridization has been shown to be an excellent test for HPV with a sensitivity of 97% and specificity of 93% [34].…”
Section: Discussionmentioning
confidence: 99%
“…Other centres choose to test for p16 alone, followed by further direct HPV testing if p16 results are unclear or negative [30][31][32]. Research groups have also looked into other molecular markers that may act as further prognostic and/or treatment factors, such as Bcl2 [33]. Recently, RNA in situ hybridization has been shown to be an excellent test for HPV with a sensitivity of 97% and specificity of 93% [34].…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical expression of p16 in oropharyngeal samples is highly correlated with hpv status 14,15 and is used in many centres throughout Canada because it is inexpensive and easily implemented in any pathology lab. Although most opcs are clearly positive or negative by p16 immunohistochemistry, ambiguous staining patterns are not infrequent 15 .…”
Section: • the Samples Obtained Reflect A Relatively Smallmentioning
confidence: 99%
“…Other methods include conventional pcr, which appears to yield a high rate of false positives 15 , in situ hybridization, and real-time pcr. The authors have had experience with in situ hybridization and have previously demonstrated a very high correlation with p16 status 14 ; however, other investigators have reported difficulties optimizing the assay and a poorer correlation with p16 and E6/ E7 expression 15 . We currently favour real-time pcr, with all samples tested in triplicate and repeated if any discrepancies arise.…”
Section: • the Samples Obtained Reflect A Relatively Smallmentioning
confidence: 99%
“…A small minority of HPV+ OP SCC show atypical clinical behavior following treatment including poor OS, DSS and Disease free survival (DFS) (12,26,27). Some cases may be associated with multicentric disease in the mucosa of the upper aerodigestive tract excluding the oral cavity.…”
Section: Hpv-related Squamous Cell Carcinomamentioning
confidence: 99%
“…However, certain relevant molecular profiles have been proposed. These include over-expression of Bcl2, EGFR, and BclxL, (27,30,31). EGFR is a transmembrane tyrosine kinase, its function affects cell cycle progression, apoptosis, angiogenesis, tumor cell mobility and metastasis.…”
Section: Hpv-related Squamous Cell Carcinomamentioning
confidence: 99%